A Randomized Crossover, Pilot Study Examining the Effect of Acupuncture in the Management of Competitive Anxiety in Athletes - Mohammad Khojastefar; Maryam Selk-Ghaffari; Amir-Hossein Memari; Farzin Halabchi; Tohid Seif-Barghi (Medical Association of Pharmacopuncture Institute, 2021)
Background : Excessive competitive anxiety induces adverse effects on athletic performance and planning efficient management methods is crucial. Objectives: We aimed to assess the effects of acupuncture on competitive anxiety. Methods : In this cross-over study, 20 male soccer players under 21 years (U-21) were randomized equally into acupuncture or control groups. The acupuncture group received acupuncture on fifteen anxiety-related points and the control group received acupuncture on fifteen points unrelated to anxiety for thirty minutes. We measured the participants' resting heart rate and galvanic skin conduction and asked them to answer the Competitive State Anxiety Inventory-2 (CSAI-2) questionnaire at baseline and the end of the intervention. Results : We detected a significant treatment effect in the cognitive anxiety level (-1.05 ± 0.91; p = 0.02) but not in the somatic anxiety level (-0.46 ± 1.68; p = 0.43), Sport Self-Confidence (-1.06 ± 2.21; p = 0.11), heart rate (0.20 ± 2.2; p = 0.93), and skin conductance (-0.50 ± 0.77; p = 0.19). Conclusion : Based on these results, acupuncture might decrease cognitive anxiety but might not affect somatic anxiety.